Timing of puberty and physical growth in obese children: a longitudinal study in boys and girls. Issue 4 (27th May 2013) - De Leonibus, C.; Marcovecchio, M. L.; Chiavaroli, V.; de Giorgis, T.; Chiarelli, F.; Mohn, A.
Summary What is already known about this subject There is emerging evidence suggesting that childhood obesity may influence the timing/tempo of puberty and growth patterns. An earlier onset of puberty generally occurs in obese girls, whereas conflicting data are available for boys. Obese children tend to be taller during pre‐puberty but lose this growth advantage during puberty. What this study adds Obese boys and girls present an earlier onset of puberty and completion of puberty, with a shorter duration of puberty compared to normal‐weight peers. Obese children tend to have a similar adult height compared to normal‐weight children. Background There is emerging evidence suggesting that childhood obesity may influence the timing of puberty and growth patterns. However, there are scant and controversial data in this field. Objective To assess whether puberty and physical growth vary in obese when compared to normal‐weight children. Methods One hundred obese pre‐pubertal children (44 boys; mean age (±SD): 9.01 ± 0.62 years; 56 girls; 8.70 ± 0.57 years) were compared to 55 normal‐weight controls (27 boys; 9.17 ± 0.26 years; 28 girls; 8.71 ± 0.62 years). All study participants were followed prospectively with 6‐monthly follow‐up visits. At each study visit, height, weight, body mass index (BMI) and pubertal stage were assessed. Results Obese children entered puberty and achieved later stages of puberty earlier than controls (onset of puberty: boys: 11.66 ± 1.00 vs. 12.12 ± 0.91 years, P = 0.049; girls: 9.90 ± 0.78 vs. 10.32 ± 1.70, P = 0.016; late puberty: boys: 13.33 ± 0.71 vs. 14.47 ± 1.00 years, P < 0.001; girls: 11.54 ± 0.99 vs. 12.40 ± 1.02, P = 0.001). Pre‐pubertal BMI standard deviation score (SDS) was inversely associated with both age at the onset of puberty (β = −0.506, P < 0.001) and age at late puberty (β = −0.514, P < 0.001). Obese children also showed an earlier age at peak height velocity (PHV) (boys: 12.62 ± 0.82 vs. 13.19 ± 0.96 years, P = 0.01; girls: 11.37 ± 0.89 vs. 12.77 ± 0.76, P < 0.001) and a lower PHV (boys: 7.74 ± 1.49 vs. 9.28 ± 1.64 cm year−1, P < 0.001; girls: 7.60 ± 1.64 vs. 8.29 ± 1.03, P = 0.03). Height SDS progressively declined over the study period in the obese group (P for trend <0.001), whereas there were no significant changes in the control group (P for trend = 0.5). Conclusions Obese boys and girls presented an earlier onset of puberty and completion of puberty and an impaired height gain during puberty.